The Correlation Between ABPM Parameters and Left Ventricular Hypertrophy in Pediatric Essential Hypertension - Wu, Haojie; Shi, Lin; Lin, Yao; Zheng, Tong (Frontiers in Pediatrics, 2022)
Objective: The aim of this study was to explore the association of dipping pattern and blood pressure load with left ventricular hypertrophy in children and adolescents with essential hypertension. Methods: Echocardiography and ambulatory blood pressure monitor data were analyzed in 425 untreated children who were diagnosed with essential hypertension. All children were divided into two groups based on echocardiography results, one diagnosed with left ventricular hypertrophy (LVH, N=140) and the other not (n-LVH, N=285). The dipping pattern and blood pressure load were calculated and compared between two groups. Multivariable logistic regression analysis was used to determine the effect of blood pressure load on LVH. Results: No significant difference was found for systolic or diastolic blood pressure dipping pattern between two groups (49.3% vs 42.1%, P=0.161; 42.9% vs 44.6%, P=0.139). LVH group had higher 24 h systolic load, daytime systolic load, nighttime systolic load and nighttime diastolic load [50%(31%,71%) vs 41%(20%,62.5%), P＜0.05; 61.5%(37.25%,83%) vs 52%(23%,74.5%), P＜0.05; 20%(0,40%) vs 0(0,33%), P＜0.05; 0(0,20%) vs 0(0,17%), P＜0.05]. Male, obesity and 24 h systolic load are independent risk factors for LVH according to stepwise logistic regression analysis in our population. Conclusion: Our results suggest a trend toward an association between blood pressure load and left ventricular hypertrophy, in which 24 h systolic load seems to be a better prognostic parameter for left ventricular hypertrophy. These findings demonstrate the importance of systolic load in discovering the risk of left ventricular hypertrophy early in children with essential hypertension.